The association between PAI-1 -675 4G/5G polymorphism and type 2 diabetes mellitus - Chen, L.; Li, S-Y.; Liu, M. (Cellular and Molecular Biology, 2017)
In this study, we aimed to analyze the association between plasminogen activator inhibitor 1 (PAI-1) -675 4G/5G polymorphism and type 2 diabetes mellitus (T2DM) risk. We included in 187 T2DM patients and 186 heathy controls between 2014 and 2017 from Tianjin Gong An Hospital, China. All patients and controls were ethnically Chinese Han population. The primers and polymerase chain reaction (PCR) conditions were performed. Results from this case-control study suggested that PAI-1 -675 4G/5G polymorphism was not associated with T2DM risk in four genetic models. Additionally, PAI-1 -675 4G/5G polymorphism was not associated with clinical and laboratory characteristics, such as age, gender, body mass index, systolic blood pressure, diastolic blood pressure, total cholesterol, triglycerides, and HbA1c. In conclusion, this case-control study suggested that PAI-1 -675 4G/5G polymorphism was not associated with T2DM risk in this population.